Engendering trade - Do, Quy-Toan; Levchenko, Andrei A.; Raddatz, Claudio (2012)
The authors analyze the interaction between a country's world market integration and its attitude towards gender roles. They discuss both theoretically and empirically how female empowerment is a source of comparative advantage that shapes a country's response to trade opening. Reciprocally, the authors show that as countries integrate into the world economy, the costs and benefits of gender discrimination shift. Their theory goes beyond a potential aggregate wealth effect associated with trade opening, and emphasizes the heterogeneity of impacts. On the one hand, countries in which women are empowered -- measured by fertility rates, female labor force participation or female schooling -- experience an expansion of industries that use female labor relatively more intensively. On the other hand, the gender gap is smaller in countries that export more in relatively female-labor intensive sectors. In an increasingly globalized economy, the road to gender equality is paradoxically very specific to each country s productive structure and exposure to world markets.